Growth, upper arm anthropometry and serum 25-hydroxyvitamin d status of brazilian and nigerian school-aged children with sickle cell disease - Adegoke, Samuel Ademola [UNIFESP] (2016)
BACKGROUND: Sickle cell disease (SCD) phenotype is very variable and many genetic and environmental modulating factors including nutritional status have been implicated. Comparative studies of patients in different socio-geographic and ecological zones afford an opportunity to investigate potential environmental and other factors that influence the phenotype. OBJECTIVES: To assess the growth parameters, upper arm anthropometry, and serum 25-hydroxyvitamin D (25-OHD) of two cohorts of children with SCD at the University Teaching Hospitals in Ile-Ife/Ilesa, Southwest, Nigeria, and Sao Paulo, Brazil. In addition, the study also sought to determine the influence of hydroxyurea (HU) on growth and nutritional status. Relationship between serum 25-OHD and disease phenotypes (rates of pain episodes, biomarkers of intravascular haemolysis and inflammatory cytokines) was also determined. METHODS: Sociodemographic, clinical, growth and upper arm anthropometry of school-aged Brazilian and Nigerian children with SCD as well as age- and sex-matched haemoglobin AA Nigerian controls were assessed. Haematological and biochemical parameters (serum 25-OHD inclusive); and inflammatory cytokines were determined by standard techniques. Relationships between serum 25-OHD, pain rates and cytokines were determined by statistical tests. Nigerian SCA children with suboptimal 25-OHD were given 2,000 IU of vitamin D3 supplemetation daily for three months and its infuence on cytokine profiles was evaluated. RESULTS: A relatively high proportion of the children in both centers (23.5 percent) were underweight. Weight, BMI-Z score, height for age-Z score, upper arm fat area and fat percentage were significantly lower in the Nigerian than Brazilian cohorts. A higher proportion of Nigerian patients (29.5% against 19.3%) were underweight, and of short stature (12.6% vs. 3.7%), while a higher proportion of Brazilian patients were overweight or obese, (9.2% vs. 4.3%) and taller for age, (16.5% vs. 8.4%). None of the Nigerian patients had severe vitamin D deficiency and only 12.6% had suboptimal vitamin D levels, however, 3.7% of the Brazilian patients had severe deficiency and majority, 79.8% had either vitamin D deficiency or insufficiency. Underweight and severe vitamin D deficiency were more prevalent among Brazilian children who were hydroxyurea-naive than those who had used HU for at least 12 months (30.6% vs. 13.7%, p = 0.036; and 11.4% vs 0%, p = 0.008 respectively). Their mean serum 25-OHD was also lower than the HU group, 20.80 ± 7.48 ng/ ml vs. 24.52 ± 8.26 ng/ml, p = 0.021. All Nigerian children with suboptimal vitamin D compared to 69.7% of those with normal vitamin D experienced vasoocclusive pain episodes in the preceding 12 months, p = 0.037, 95% CI = 0.7 ? 0.9. The mean serum vitamin D of those with at least one pain episode (41.25 ± 10.09 ng/mL), was significantly lower than 45.22 ± 7.71 ng/mL for those without pain episode, p = 0.043, 95% CI = 1.3 ? 7.8. After excluding the potential influence of HU, among Brazilian patients, hemoglobin and hematocrit had significant positive correlations with serum 25-OHD (r = 0.40, p = 0.017 and r = 0.45, 0.006 respectively), while reticulocyte percentage, absolute reticulocyte count and serum lactate dehydrogenase (LDH) had significant inverse correlation (r = -0.44, p = 0.008; r = -0.47, p = 0.007 and r = -0.45, p = 0.007 respectively). Also, the mean hemoglobin of those with suboptimal vitamin D was lower (8.1 ± 0.9g/dl vs. 9.4 ± 1.8g/dl, p = 0.014), while the mean reticulocyte count and serum lactate dehydrogenase were significantly higher, p = 0.047 and 0.003 respectively.Compared to those with normal level, Nigerian patients with suboptimal 25-OHD had significantly higher serum pro-inflammatory cytokines IL-6, 8 and 18 (p = 0.003, 0.010 and 0.002 respectively) and lower levels of anti-inflammatory cytokine IL-11 (p = 0.005). Proinflammatory cytokines IL-2, 6, 8, 17 and 18 were reduced significantly while antiinflammatory cytokines IL-11 was significantly higher at the end of 3 months of vitamin D3 supplementation. CONCLUSIONS: Nigerian children with SCD were lighter, shorter and had less fat than their Brazilian counterparts. On the contrary, more Brazilian children had overweight/ obesity, with majority having suboptimal serum 25-OHD levels. HU therapy tends to protect against growth retardation and vitamin D deficiency. A possible association between depressed serum vitamin D level and increased frequency of acute pain episodes supports the role of vitamin D in musculoskeletal health. Also the correlation between serum 25-OHD levels and biomarkers of intravascular haemolysis and inflammation suggest its role in the pathogenesis of haemolytic and inflammatory phenotypes in children with SCD.